The Importance of Financial Metrics in Physician Funding and Performance Evaluation. Issue 5 (27th April 2021) - Patrinely, J. Randall; Walker, Sallie H.; Glassman, Gabriella E.; Davis, Matthew J.; Abu-Ghname, Amjed; Khan, Umraz; Drolet, Brian C.; Forte, Antonio J.; Perdikis, Galen
Abstract : Background: Financial key performance indicators are often used to evaluate performance. Understanding of key performance indicators can be crucial for career advancement and bargaining leverage in resource negotiations. This study aimed to identify the most important key performance indicators used in surgical funding requests and understand how to use these metrics in clinical practice. Methods: In two tertiary medical centers, funding requests for surgeon gap support (2019 to 2020) and equipment (2017 to 2019) within departments of surgery were reviewed. The requesting department, approval status, and amount allotted were recorded. In requests for gap support, projections for contribution margin, operating room volume, charges, collections, and relative value units were tracked. Projected contribution margin and cost savings were recorded for equipment funding requests. Results: There were 40 gap support and 24 equipment requests, and all were approved. Most gap support requests included collections (90.0 percent), charges (87.5 percent), operating room cases (80.0 percent), relative value units (77.5 percent), and hospital contribution margin (77.5 percent). The most represented departments were general surgery (37.5 percent), neurosurgery (22.5 percent), and plastic surgery (15.0 percent). The departments that submitted the most equipment requests were general surgery (28.0 percent) and neurosurgery (28.0 percent). Most requests included projections for contribution margin (95.8 percent) and cost savings (87.4 percent). Projected hospital contribution margin correlated with the amount of funds allotted for surgeon support ( r = 0.409; p = 0.022). Conclusions: This multicenter study identified the importance of using key performance indicators for a successful financial outcome in funding requests. In addition, the authors demonstrate the need for surgeons to understand their own key performance indicators. Surgeons should advocate for increased transparency to better understand their financial contributions and performance.